On topological integer additive set-labeling of star graphs - Hafizh M. Radiapradana; Suhadi Wido Saputro; Erma Suwastika; Oki Neswan; Andrea Semanicova-Fenovcıkova (Electronic Journal of Graph Theory and Applications (EJGTA), 2018)
For integer k ≥ 2, let X = {0, 1, 2, …, k}. In this paper, we determine the order of a star graph K1, n of n + 1 vertices, such that K1, n admits a topological integer additive set-labeling (TIASL) with respect to a set X. We also give a condition for a star graph K1, n such that K1, n is not a TIASL-graph on set X.